2005
DOI: 10.1080/07373930500210473
|View full text |Cite
|
Sign up to set email alerts
|

Final Drying of Whole Milk Powder in Vibrated-Fluidized Beds

Abstract: Vibro-fluidized beds are widely used in drying sticky powders and agglomerated materials as milk powder. Using a vibro-fluidized laboratory scale dryer, this work is aiming at analyzing preliminarily the effect of its operational variables on the drying kinetics and characteristics of whole milk powder. The full-factorial design technique with three replications at the central point has been employed to generate data and correlations to quantify the effect of inlet air temperature, air flow rate, and vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Meanwhile, the moisture was gradually evaporated until the moisture approached to the critical moisture content. These similar drying processes were also reported in both the drying of coal and of other solids [44,45]. Moreover, as increasing the inlet temperature, the evaporation process was accelerated and the drying times reduced.…”
Section: Effect Of Minerals On the Drying Kineticssupporting
confidence: 50%
“…Meanwhile, the moisture was gradually evaporated until the moisture approached to the critical moisture content. These similar drying processes were also reported in both the drying of coal and of other solids [44,45]. Moreover, as increasing the inlet temperature, the evaporation process was accelerated and the drying times reduced.…”
Section: Effect Of Minerals On the Drying Kineticssupporting
confidence: 50%
“…flowability, density, dissolution, and dispersion characteristics) of powder, thereby reducing the tendency of powder to caking (Mukherjee & Bhattacharya, 2006). Cruz, Passos, and Ferreira (2005) also reported that the moisture content of the whole milk and skim milk powders was decreased from 6-7%-3% and 4% by applying the fluidized bed drying.…”
Section: Moisture Contentmentioning
confidence: 98%
“…The wet concentrate droplets collide with the fines and stick together, forming larger, irregular shaped ''agglomerates". After drying and cooling in the vibrating fluidized bed(s), the powder is then conveyed to packaging operations and is stored until its end use (Pearce;Singh and Newstead, 1992;Cruz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%